Inflammatory Bowel Disease Outcomes Following Fecal Microbiota Transplantation for Recurrent C. difficile Infection. Issue 9 (6th November 2020) - Allegretti, Jessica R; Kelly, Colleen R; Grinspan, Ari; Mullish, Benjamin H; Hurtado, Jonathan; Carrellas, Madeline; Marcus, Jenna; Marchesi, Julian R; McDonald, Julie A K; Gerardin, Ylaine; Silverstein, Michael; Pechlivanis, Alexandros; et al.
Abstract: Background: Recurrent Clostridioides difficile infection (CDI) in patients with inflammatory bowel disease (IBD) is a clinical challenge. Fecal microbiota transplantation (FMT) has emerged as a recurrent CDI therapy. Anecdotal concerns exist regarding worsening of IBD activity; however, prospective data among IBD patients are limited. Methods: Secondary analysis from an open-label, prospective, multicenter cohort study among IBD patients with 2 or more CDI episodes was performed. Participants underwent a single FMT by colonoscopy (250 mL, healthy universal donor). Secondary IBD-related outcomes included rate of de novo IBD flares, worsening IBD, and IBD improvement—all based on Mayo or Harvey-Bradshaw index (HBI) scores. Stool samples were collected for microbiome and targeted metabolomic profiling. Results: Fifty patients enrolled in the study, among which 15 had Crohn's disease (mean HBI, 5.8 ± 3.4) and 35 had ulcerative colitis (mean partial Mayo score, 4.2 ± 2.1). Overall, 49 patients received treatment. Among the Crohn's disease cohort, 73.3% (11 of 15) had IBD improvement, and 4 (26.6%) had no disease activity change. Among the ulcerative colitis cohort, 62% (22 of 34) had IBD improvement, 29.4% (11 of 34) had no change, and 4% (1 of 34) experienced a de novo flare. Alpha diversity significantly increased post-FMT, and ulcerative colitis patients became more similar to the donor than Crohn's disease patients ( P = 0.04). Conclusion: This prospective trial assessing FMT in IBD-CDI patients suggests IBD outcomes are better than reported in retrospective studies.